(3EOGQI CNWGQ TQcGJ GdJCejf (B:s (3CNWGQ GdGcJJGH , CNWGQ GdGSJKeGQ (B/s - (3CHh HcQ, YjO CMeOs ((3YeGf(B: s (3OGQ UaGA(B, s, 2011)
(3GdedGAI GdeGdjI dTQcGJ GdJCejf (B: (3eaghegG , CgejJgG h GdGNWGQ GdeDKQI ajgG , JMdjd h bjGS CNWGQ GdGcJJGH h JMdjd h bjGS eNGWQ GSJKeGQ CehGd TQcGJ GdJCejf , GOGQI GNWGQ GdGcJJGH h CNWGQ GdGSJKeGQ aj TQcGJ GdJCejfs
Keywords: (3GdTQcGJs; (3GdeNGWQ GdeUQajIs; (3TQcGJ GdJCejfs